The usage and social capital of mobile phones and their effect on the performance of microenterprise: An empirical study - Islam, Md Mazharul; Habes, Essam M.; Alam, Md Mahmudul (Elsevier Inc., 2018)
This study aims to uncover the impact of the information and communication capabilities of mobile phone use on the performance of microenterprises in Bangladesh.Data were collected from microenterprise owners through face-to-face interviews and a series of statistical analyses were used to assess the effects of mobile phone use. The results of the study show a significant direct relationship between mobile phone use, social capital, and the performance of microenterprises.Further investigation revealed that social capital and non-financial business performance variables are involved in the mediation process between the financial performance of microenterprises and the use of mobile phones.The novelty of this research lies in being the first to establish a high-level statistical relationship between the use of the mobile phone, its mediating factors, and the financial performance of microenterprises.